Classical swine fever: current situation in European countries and its potential danger for the greek pig industry - KYRIAKIS (ΚΥΡΙΑΚΗΣ Σ.Κ.), S. C.; KRITAS (Σ.Κ. ΚΡΗΤΑΣ), S. K.; PAPADOPOULOS (ΠΑΠΑΔΟΠΟΥΛΟΣ Ο.), O.; MAVROMATIS (ΜΑΥΡΟΜΑΤΗΣ Ι.), I.; TSINAS (ΤΣΙΝΑΣ Α.), A. (Journal of the Hellenic Veterinary Medical Society, 2018)
Classical swine fever is a highly contagious viral disease of substantial economical importance for the pig industry. Its clinical demonstration varies according to the virulence of the infecting strain, so that highly virulent strains cause severe acute disease, whilst strains of low virulence appear to cause only mild or even inapparent disease. Swine fever is α problem in many countries worldwide for years. In Greece, the latest case was reported during 1985. Nowdays, swine fever became once more "hot" due to its appearance in countries that were free of the disease for long periods (Holland, Spain, Italy etc). In this review paper, some general information necessary for the understanding and the prevention of the disease are presented, and the latest data of the recent epidemic in different European countries are retrieved. Finally, based on the recent "painful" experience of these countries, essential preventive measures for the greek pig industry are suggested.